Serotonin and Adenosine G-protein Coupled Receptor Signaling for Ventilatory Acclimatization to Sustained Hypoxia - Moya, Esteban A.; Powell, Frank L. (Frontiers in Physiology, 2018)
Different patterns of hypoxia evoke different forms of plasticity in the neural control of ventilation. For example, acute intermittent hypoxia produces long term facilitation (LTF) of ventilation, while chronic sustained hypoxia (CH) causes ventilatory acclimatization to hypoxia (VAH). In both LTF and VAH, ventilation in normoxia is greater than normal after the hypoxic stimulus is removed and the acute hypoxic ventilatory response can increase. However, the mechanisms of LTF and VAH are thought to be different based on previous results showing serotonin 5HT2 receptors, which are G protein coupled receptors (GPCR) that activate GQ signaling, contribute to LTF but not VAH. Newer results show that a different GPCR, namely adenosine A2A receptors and the GS signaling pathway, cause LTF with more severe intermittent hypoxia, i.e. PaO2 = 25-30 Torr for GS vs. 35-45 Torr for LTF with the GQ signaling pathway. We hypothesized adenosine A2A receptors and GS signaling are involved in establishing VAH with longer term moderate CH and tested this in adult male rats by measuring ventilatory responses to O2 and CO2 with barometric pressure plethysmography after administering MSX-3 or ketanserin (A2A and 5HT2 antagonists, respectively, both 1mg/Kg i.p.) during CH for 7 days. Blocking GS or GQ signals throughout CH exposure, significantly decreased VAH. After VAH was established, GQ blockade did not affect ventilation while GS blockade increased VAH. Similar to LTF, data support roles for both GQ and GS pathways in the development of VAH but after VAH has been established, the GS pathway inhibits VAH.